Improvement of low-speed operation performance of DTC for three-level inverter-fed induction motors - Lee, KB; Song, JH; Choy, I; Yoo, JY (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
A direct torque control algorithm for three-level inverter-fed induction motors is presented. Basic voltage selection methods similar to two-level inverter provoke some problems such as stator-flux drooping phenomenon and undesirable torque control deterioration appeared, especially at low-speed operation. To overcome these problems, an algorithm with the basic switching sectors subdivided and intermediate voltage vectors applied is proposed in this paper. This algorithm basically considers applications in which direct torque-controlled induction motors are fed by three-level inverters with maximum switching frequency lowered around 1 kHz. An adaptive observer is also employed to bring better responses at the low-speed operation, by estimating some state variables and motor parameters which take a deep effect on the performance of the low-speed operation. Simulation and experiment results verify effectiveness of the proposed algorithm.